Development of High Efficiency and Low Emission Low Temperature Combustion Diesel Engine with Direct EGR Injection - Ho R.J.; Kumaran P.; Yusoff M.Z. (Institute of Physics Publishing, 2023)
Combustion; Diesel engines; Fuels; Heptane; Ignition; Nitrogen oxides; Sustainable development; Temperature; Combustion simulations; Detailed chemical kinetic; Environmental sustainability; Fuel injection process; High efficiency and low emission; Homogeneous charge combustion ignitions; Low temperature combustion; Particulate matter formations; Direct injection; combustion; diameter; diesel engine; efficiency measurement; emission; fluid injection; fossil fuel; low temperature; natural gas; nitrogen oxides; particulate matter; reaction kinetics; research work